Long‐term efficacy of a 0.07% cetylpyridinium chloride mouth rinse in relation to plaque and gingivitis: a 6‐month randomized, vehicle‐controlled clinical trial. Issue 2 (15th July 2014) - Van Leeuwen, MPC; Rosema, NAM; Versteeg, PA; Slot, DE; Van Winkelhoff, AJ; Van der Weijden, GA
Abstract: Objective: To evaluate the effectiveness of 0.07% cetylpyridinium chloride (CPC) mouth rinse for reduction of gingival inflammation and inhibition of plaque compared to a vehicle control (VC) mouth rinse over a 6‐month period. Materials & Methods: Participants ( n  = 62) used their randomly assigned product as adjunct to toothbrushing. Bleeding, plaque and staining scores were assessed at baseline, 3 and 6 months. Plaque and saliva samples were taken at each assessment monitoring possible shifts in the composition of the microbiota. Results: A significant difference ( P  = 0.002) in favour of the CPC mouth rinse, with respect to plaque scores, was found. Bleeding scores at 6 months were not significantly different ( P  = 0.089). However, when correcting for baseline values, a tendency towards a significant difference in bleeding scores at end trail was observed in favour of the CPC mouth rinse ( P  = 0.061). Regarding staining at 3 and 6 months, a small but significant difference (8.6% and 10.4%, respectively) ( P  < 0.0001) was observed with lower scores for the VC group. There was a significant reduction in total anaerobic count in the CPC group at 6 months ( P  < 0.05). The ratio of aerobes/anaerobes was markedly increased at 3 months, especially in the CPC group. No further differences were observed between groups at 6 months. Conclusions: The use of 0.07% CPC mouth rinse was significantly more effective in reducing plaque scores than the vehicle control. Bleeding scores were not different at 6 months. The test product was well accepted and did not cause any serious clinical side effects or negatively affected the microbiota.